Peran Lingkungan dalam Pendidikan Karakter - Mar’atun Solehah (Lembaga Bale Literasi, 2023)
Character education is a guidance to build new attitude and behavior, to develop and to change gift attitude, behavior and habit better that before to establish safe, comfortable, and harmonic environment and life for our self and others. This article writing is aimed to present about character education and its influence of environment toward the process and crop of the character education that include three environments such as family, social, and school. Analysis method used in this article is with rational approach based on library observation by reading some books and articles to gain data needed. Based on this study result, every environment have crucial position in influencing someone’s charcater so good environment is a must to support succession of character education. And also using proper method of character education has important role on it. There are some ways offering by Imam Al-Ghazali in his book Ayyuhal Walad that proved effectively growing and developing someone’s character.